The Specifics of Social and Cultural Determination of the Current Economic Activity - Vodenko, Konstantin V.; Cherkesova, Elvira Y.; Shvachkina, Lyudmila A.; Fateeva, Svetlana V.; Erosheva, Irina Y. (International Journal of Economics and Financial Issues, 2016)
The paper considers the problems of modern economic activities in the socio-cultural context. We study the differences of methodological approaches to the specific understanding of the socio-economic development (in the face of a materialist method of Marx and the method of interpretive sociology M. Weber). The conclusion is that at the present time there is awareness of the need for cultural, ethical and religious institutions in shaping economic behavior in the context of the methodology of Max Weber. The specific character of philosophical concepts which should underlie modern economic activity. It is noted that such philosophical categories as morality, human-dimension, socio-cultural specificity should be the basis of a modern economy. economic development philosophy appears as a philosophy of social wealth, access to, and use of the population for the development of human capital. Keywords: economics, philosophy, society, morality JEL Classifications: Ð’41, Z13